Reframing Public Sector Accounting through Digital Nutrition Programs: Evidence from the Rapor MBG - Khaerun Nisa SH; Andi Nurul Tenriwali Hasanuddin; Andi Rezki Nurhikmah; Andi Shahifah Muthahharah (Politeknik Caltex Riau, 2026)
Main Purpose - This study examines how the Rapor MBG platform reshapes accountability within Indonesia’s Free Nutritious Meal Program. Method - Using a qualitative case study at the Manggala Kitchen in South Sulawesi, data were gathered through application observations, document analysis, and interviews. Informants comprised fifteen stakeholders, including regional coordinators, financial verifiers, school coordinators, and grassroots kitchen managers. Main Findings - The findings reveal that accountability is heavily driven by rigid metrics, specifically automated budget-caps, midnight photo-upload deadlines, and fixed cost-per-portion calculations. Although this standardizes central audit readiness, fieldwork shows it forces local operators to artificially adjust manual vendor invoices and lower food quality to prevent automated funding freezes. Consequently, the system creates a symbolic dashboard that successfully satisfies bureaucratic oversight but systematically marginalizes qualitative nutritional outcomes and local operational flexibility. Theory and Practical Implications - This study proves that digital accounting infrastructures act as constitutive forces that dictate organizational behavior rather than serving as neutral reporting tools. Practically, system designers must replace rigid drop-down menus with dynamic local pricing matrices and integrate digital beneficiary feedback loops to protect operational survival. Novelty - Unlike prior studies focusing on general policy effectiveness, this research uniquely uncovers how digital accounting software actively constructs and constrains micro-level accountability realities.